1998
DOI: 10.1038/sj.onc.1201621
|View full text |Cite
|
Sign up to set email alerts
|

A transgenic mouse model for mammary carcinogenesis

Abstract: Missense mutations in the p53 tumor suppressor occur frequently in human breast cancer and in¯uence both the prognosis and response to chemotherapy. Amino acid 175 (equivalent to murine 172) is the second most common site of missense mutations in p53 in human breast cancer. Over 95% of these mutations are arginine-to-histidine (R-H) substitutions resulting in a gain-of-function, and not merely a dominant-negative phenotype. Transgenic mice expressing a p53 172 R ± H construct targeted to the mammary gland by m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
86
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 87 publications
(92 citation statements)
references
References 41 publications
6
86
0
Order By: Relevance
“…The p53 172R-H mice develop few spontaneous mammary tumors. However, susceptibility to mammary tumorigenesis is markedly increased in p53 172R-H mice following treatment with the carcinogen DMBA (Li et al, 1998) or with coexpression of oncogenes such as neu (Li et al, 1997). This supports the suggestion that this gain-of-function mutant is capable of cooperating with a number of di erent factors known to in¯uence mammary tumorigenesis.…”
Section: Introductionsupporting
confidence: 71%
See 4 more Smart Citations
“…The p53 172R-H mice develop few spontaneous mammary tumors. However, susceptibility to mammary tumorigenesis is markedly increased in p53 172R-H mice following treatment with the carcinogen DMBA (Li et al, 1998) or with coexpression of oncogenes such as neu (Li et al, 1997). This supports the suggestion that this gain-of-function mutant is capable of cooperating with a number of di erent factors known to in¯uence mammary tumorigenesis.…”
Section: Introductionsupporting
confidence: 71%
“…Previous studies (Li et al, 1998;Wang et al, 1998) have demonstrated aneuploidy in both mammary and skin tumors occurring in DMBA-treated mice carrying a targeted p53 172R-H transgene. To determine if p53 172R-H expression results in a predisposition to aneuploidy in the context of the WAP-DES transgene, FACS analysis was conducted on tumor cell nuclei.…”
Section: Mechanism Of Synergymentioning
confidence: 98%
See 3 more Smart Citations